Development of Aqidah Akhlak Learning Media "Board Game Based on Education Fun on the Theme of Commendable Morals (E-Fun A2M)" for High School Students - Desta Pradana, Mochamad; Owa-Onire Uthman, Yusuf Olawale (Assyfa Learning Journal, 2023)
Monotonous learning patterns lead to ineffective learning behavior which impacts on learning outcomes. Lack of teacher creativity and mastery in processing learning will make students reluctant to take part in learning. The use of learning media as a support for learning is not optimal. The purpose of this study was to develop Board Game Learning Media based on Commendable Morals Education Fun (E-Fun A2M) in Akidah Akhlak High School subjects. This research is research development or Research and Development (R&D) with the Thiagarajan, Semmel and Semmel models by testing the validity of A2M's E-Fun learning media. This is intended to determine the practicality and effectiveness. The specialty of this research is research and development based on the four-D development model (Define, design, develop, disseminate). However, due to the limitations of researchers, this development only reached the develop stage. The research subjects were six students of class X. The instruments used were validation sheets, teacher and student response questionnaires, and student learning outcomes tests. The survey results show that the relevance score of E-Fun A2M learning media is in the very valid category with a value of 92.5%. This shows that the E-Fun A2M learning media can be used by students as a learning medium for Aqidah Akhlak